Pelatihan Pengolahan Sampah Organik Menjadi Pupuk Padat dan Cair Di Bank Sampah Sultan Tanjung Kabupaten Lombok Timur - As'urin, B.; Sulastri, Sulastri; Junaidi, Junaidi (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2025)
Organic waste is an ongoing problem both in big cities and in villages. Along with the increasing population and lack of awareness of environmental damage due to ineffective waste management. Therefore, the government and the community have the task of completing waste management related training on managing organic waste into solid and liquid fertilizer at the Sultan Tanjung Waste Bank, East Lombok Regency, which was held to increase knowledge, skills and empower the community in effective and efficient waste management in Tanjung Village. . The service implementation team collaborates with LP2M as a resource person in the training. The results obtained from this service are as follows: a). This service received a positive response from the management of the Tanjung Sultan waste bank and the training participants (community) of Tanjung Village, however, further development and assistance is needed. b). Achieving an increase in public knowledge regarding the management of organic waste into solid and liquid fertilizer. c). There is a need to develop professional waste management.